2018
DOI: 10.1155/2018/5701638
|View full text |Cite
|
Sign up to set email alerts
|

Dentine Tubule Occlusion by Novel Bioactive Glass-Based Toothpastes

Abstract: There are numerous over-the-counter (OTC) and professionally applied (in-office) products and techniques currently available for the treatment of dentine hypersensitivity (DH), but more recently, the use of bioactive glasses in toothpaste formulations have been advocated as a possible solution to managing DH. Aim. The aim of the present study, therefore, was to compare several bioactive glass formulations to investigate their effectiveness in an established in vitro model. Materials and Methods. A 45S5 glass w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
2
18
1
1
Order By: Relevance
“…ion [19] in the apatite structure of enamel. The FAP is known to have better chemical stability and lesser bioresorption rate than HAP [20]. Fluoride is quite effective in enamel remineralization, but its effect on DH is rather limited [21].…”
Section: Discussionmentioning
confidence: 99%
“…ion [19] in the apatite structure of enamel. The FAP is known to have better chemical stability and lesser bioresorption rate than HAP [20]. Fluoride is quite effective in enamel remineralization, but its effect on DH is rather limited [21].…”
Section: Discussionmentioning
confidence: 99%
“…Once BGN powder comes into contact with a biological fluid, such as saliva, it releases sodium and calcium ions and increases pH, thereby creating an alkaline environment [17]. In an alkaline environment, calcium and phosphate ions form an apatite that occludes the dentinal tubule and diminishes fluid movement within the dentinal tubule [18]. Recent studies reported successful dentinal tubule occlusion and dentin remineralization using BGN.…”
Section: Introductionmentioning
confidence: 99%
“…This recently introduced formulation has not been extensively researched by clinicians and researchers. Currently, there appears to be limited in vivo studies on BioMin‐F, although several in vitro studies have published. Therefore, as a result of the limited data available that would support the efficacy of this formulation it was considered appropriate to conduct a study to evaluate the efficacy of BioMin‐F for the treatment of DH.…”
Section: Introductionmentioning
confidence: 99%